The East Asian Crisis : Macroeconomic Developments and Policy Lessons - Kochhar, Kalpana (IMF Working Papers; Working Paper ;, 1998)
This paper reviews macroeconomic developments during the first year of the crisis in east Asia and draws some preliminary policy lessons. The crisis is rooted in the interaction of large capital inflows and weak private and public sector governance. At the same time, macroeconomic adjustment in these countries has resulted in some surprising outcomes, including severe economic contractions, low inflation, and rapid external adjustment. The lessons for crisis resolution include the importance of tight monetary policy early on for exchange rate stabilization, flexible fiscal policy, and comprehensive structural reform. Crises are avoided by prudent macroeconomic policies, diligent bank supervision, transparent data dissemination, strong governance, and forward-looking policymaking, even in good times.